Autophagy in cardiovascular biology - Lavandero, Sergio (J Clin Invest, 2015)
Cardiovascular disease is the leading cause of death worldwide. As such, there is great interest in identifying novel mechanisms that govern the cardiovascular response to disease-related stress. First described in failing hearts, autophagy within the cardiovascular system has been widely characterized in cardiomyocytes, cardiac fibroblasts, endothelial cells, vascular smooth muscle cells, and macrophages. In all cases, a window of optimal autophagic activity appears to be critical to the maintenance of cardiovascular homeostasis and function; excessive or insufficient levels of autophagic flux can each contribute to heart disease pathogenesis. In this Review, we discuss the potential for targeting autophagy therapeutically and our vision for where this exciting biology may lead in the future.